Sprejemanje poslovnih informacijskih rešitev in digitalna transformacija v podjetjih - Sternad Zabukovšek, Simona; Bobek, Samo (University of Maribor Press, 2023)
Acceptance of Business Information Solutions and Digital Transformation in Companies. Acceptance of newly introduced IT/IS by users is critical for the successful use of IT/IS. Adoption is defined as a positive perception of IT/IS, consequently, a positive decision by the individuals who use them. A common question among researchers is why some new IT/IS are better accepted than others. Therefore, the book’s first chapter focuses on the bibliometric analysis of scientific publications in IT/IS adoption for digital transformation. Further, the development and sharing of IT/IS adoption models and theories are highlighted, where we are limited to technology acceptance models. The most important IT/IS adoption models used for adopting business information solutions were researched and presented in the second chapter of the scientific monograph. Due to the complexity of the ERP solution and the unsuccessful implementation of these, few studies have been conducted in the past that would address the adoption of the technology from the perspective of individual users, including several influencing factors. This was the primary problem based on which we prepared and researched the Business Information Solutions Adoption Model (ERPAM), presented in the third chapter of the scientific monograph, together with important findings that we came on more than ten years of research in this field.